FAKTOR RISIKO PENYEBAB GANGGUAN MENTAL DALAM NOVEL LEBIH SENYAP DARI BISIKAN KARYA ANDINA DWIFATMA - Kurniati, Mulia (HISKI, 2025)
After getting married and having children, generally, women from the lower middle class become the ones with the most sources of stress. However, many women are forced to remain silent and compromise with their problems because society considers marital issues to be a disgrace, too domestic, and vulgar to be discussed. This causes many women to suffer from depression in silence because the causes of their mental health issues are often overlooked. With a literary psychology approach and Stuart's stress adaptation theory, this research aims to identify the risk factors causing mental disorders in the female protagonist of the novel